An Analysis of speech Act in Shakira's Speech at Wise Conference Qatar - Yuspik; Salsabila; Erlina, Ida Ayu Hani; Hans, Diah Maulidya; Praditya, Dion Wildan (Department of English Education, Universitas Panca Sakti Bekasi, 2023)
The aim of this research was to know the types of speech act and the most speech act find in Shakira’s speech through watching the video and reading script. This speech was delivered at WISE Conference Qatar on 2019 with the title “Education Changes the World”. The data was taken from the YouTube. This research used descriptive qualitative method to describe and analyze the type of speech act and the most speech act used in Shakira’s speech. To focus on this research, the researcher limited the type of speech act (illocutionary act) based on John Searle’s theory to know the types of speech act and after that analyzed the most speech act used in the speech. The study found types of speech act. The details of speech act in Shakira’s speech are 23 data which were divided into five categories, as follow; 70% is assertive, 5 or 15% is directive, 3 or 9% is expressive, 2 or 6% is commisive, but declaration were not found in this research. Then, assertive is the most dominant type that used in this speech.